Penerapan Teknik Self-Management Untuk Mereduksi Stres Akademik Mahasiswa UNUGIRI Bojonegoro Pada Masa Pandemi Covid-19 - Novitasari, Zeti; Cahyaningrum, Vesti Dwi (Nusantara of Research : Jurnal Hasil-hasil Penelitian Universitas Nusantara PGRI Kediri, 2021)
The Covid-19 pandemic has made learning held online and requires students to be more active. This expectation turns out to make students' academic stress increase. This phenomenon also occurs in UNUGIRI students which are characterized by students getting bored more quickly and their lack of time for interpersonal relationships. One of the things that are planned to be able to reduce this is by using self-management techniques. Thus, the purpose of this study was to determine the effectiveness of self-management techniques in reducing academic stress. To achieve this goal, this study uses the pretest and posttest control group design methods. Of the 66 students who were used as research subjects, 12 students were selected who were indicated to experience academic stress and were then designated as the sample of this study. The results of the study, which were analyzed using the Mann-Whitney technique, showed that the Asymp.Sig score. (2-tailed) was at 0.004 (0.004<0.05). These results indicate that self-management techniques are effective in reducing student academic stress.